Importance of Arterial Conduit Function Assessment in Chronic Congestive Heart Failure: Predictors of True Circulatory Decompensation for Optimal Timing of Mechanical Circulatory Support - Siniawski, Henryk; Hetzer, Roland (IntechOpen, 2011)
None